UNDERSTANDING OF NIRUHABASTI: COMPILATION FROM SUSHRUTA SAMHITA (AYUSHDHARA, 2020)
Basti is a special treatment of Ayurveda, among Panchakarma therapies. According to Bruhatrayee, Basti therapy is the best when we treat Vata related disorder. Basti has both preventive and curative perspectives. Basti describes as Ardha Chikitsa, because being the best in maintaining quality and quantity of life. Basti when used properly promotes physical development, complexion, strength, immunity and life span. Bruhatrayee described various types of Basti. Among various types of Basti, Niruha Basti is important type described by all Acharya. There are various opinions about Niruha Basti, its types, method of preparation, indications, contraindications, complications and uses. The present article is an attempt to compile information about Niruha Basti according to Sushruta.